Learning and intelligent optimization : 9th International Conference, LION 9, Lille, France, January 12-15, 2015. Revised selected papers /: 9th International Conference, LION 9, Lille, France, January 12-15, 2015. Revised selected papers. (2015) - Unknown
No abstract available